Metabolic reserves of diapausing western cherry fruit fly (Diptera: Tephritidae) pupae in relation to chill duration and post-chill rearing conditions - Neven, Lisa G.; Yee, Wee L. (Frontiers in Insect Science, 2022)
. How different macronutrients are utilized at various stages of pupal diapause and the effects of winter length on nutrient reserves remain poorly studied for most insects. Western cherry fruit fly, Rhagoletis indifferens (Diptera: Tephritidae), is a specialist on cherries in higher latitudes or elevations in western North America that exhibits a rigid pupal diapause requiring chilling before adult development can occur. We determined the relationship between metabolic reserves and diapause status in R. indifferens pupae, testing the hypotheses that lipids are the primary reserves utilized during diapause and that long periods of warmth deplete these reserves more than periods of cold. Effects of 0- to 20-week durations at 3°C and subsequent exposure to 23°C and 16:8 L:D (warm rearing conditions) for 0 to 7 weeks on lipid, protein, carbohydrate, and glycogen reserves of R. indifferens pupae were determined. During diapause, lipid reserves were the primary source of energy utilized by R. indifferens, while protein and carbohydrate levels were stable throughout diapause and thus less utilized. At post-diapause, glycogen levels fluctuated the most, indicating that lipid reserves were converted to glycogen to support metabolism for adult fly development. Unchilled pupae did not deplete lipid reserves, unlike chilled pupae, likely because unchilled pupae remained in diapause. Rhagoletis indifferens have evolved a nutrient utilization strategy typical of rigid diapausing insects in higher latitude environments.